Land Conversion’s Impact on Food Security in Sindangsari, Karawang, Indonesia - Henny Widyastuti; Deffi Ayu Puspito Sari (Faculty of Agriculture, Merdeka University Surabaya, Indonesia, 2024)
According to the Food Security and Vulnerability Atlas (FSVA) standard, of the 309 villages in Karawang, 63 are classified as food insecure. This study aims to determine the land conversion factors that affect food security in Karawang and to identify the factors influencing food access at the farm level. Using quantitative methods, including multiple linear regression analysis and logistic regression, the results show that the variable “number of industries” has a significant impact on food security, while income per month and farming experience significantly affect food access at the farm level. Additionally, food security (represented by the percentage of the poor) and regional security (represented by the crime rate) demonstrate a linear correlation.